قياس كفاءة شركات التامين بالجزائر بأسلوب تحليل مغلف البيانات - بوزيان الرحماني, هاجر (جامعة الوادي - University of Eloued, 2022)
This study aims to measure the efficiency of the insurance companies in the Algerian insurance marketduring the year 2019. using the method of data envelopment analysis using , constant returns to scaleCRS and Variable Volume Returns (VRS), where the capital variables and general expensesweretaken as inputs. The study came to the conclusion that within of 22 insurance companies, 2companiesachieved efficiency ,SAA and CNMA companies which is inacceptable, 8 companiesachieved technical efficiency.while12 companies didn’t achieve efficiency ,Most of them focus on accident insurance.This requires opening more space for the private sector in order to achieve acceptable levels of efficiency.
MEASURING THE EFFICIENCY OF ALGERIAN INSURANCE COMPANIES USING THE METHOD OF DEA ( DATAENVELOPMENT ANALYSIS)
مقال
Keywords: كفاءة ; شركة مظلة ; مغلف البيانات ; شركة التأمين